2002
DOI: 10.4049/jimmunol.169.7.3536
|View full text |Cite
|
Sign up to set email alerts
|

Fas Resistance of Leukemic Eosinophils Is Due to Activation of NF-κB by Fas Ligation

Abstract: TNF family receptors can lead to the activation of NF-κB and this can be a prosurvival signal in some cells. Although activation of NF-κB by ligation of Fas (CD95/Apo-1), a member of the TNFR family, has been observed in a few studies, Fas-mediated NF-κB activation has not previously been shown to protect cells from apoptosis. We examined the Fas-induced NF-κB activation and its antiapoptotic effects in a leukemic eosinophil cell line, AML14.3D10, an AML14 subline resistant to Fas-mediated apoptosis. EMSA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
2
25
1
Order By: Relevance
“…In support of this notion, the critical role of NF-kB in the resistance against apoptotic signal in various cell types has been demonstrated. For example, blocking NF-kB activation is found to convert the survival agent into an apoptotic effector in Jurkat leukemic T cells (23), and Fas resistance of leukemic eosinophils is shown to be due to the activation of NF-kB induced by Fas receptor ligation (47). In this regard, we have noted a transient induction of NF-kB activation upon Fas ligation in Jurkat T cells, which is then downregulated as apoptosis proceeds (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…In support of this notion, the critical role of NF-kB in the resistance against apoptotic signal in various cell types has been demonstrated. For example, blocking NF-kB activation is found to convert the survival agent into an apoptotic effector in Jurkat leukemic T cells (23), and Fas resistance of leukemic eosinophils is shown to be due to the activation of NF-kB induced by Fas receptor ligation (47). In this regard, we have noted a transient induction of NF-kB activation upon Fas ligation in Jurkat T cells, which is then downregulated as apoptosis proceeds (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…It suggested that delayed or inefficient induction of apoptosis via Fas should be sufficient to allow the activation of NF-B pathway. In contrast, inhibition of NF-B activation completely abrogated the resistance of leukemic eosinophils to Fas-mediated killing (40). The cells of osteoclast lineage increased the sensitivity to Fas-mediated killing (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Although signaling through the receptors for TNF-a or FasL mainly induces active apoptosis of eosinophils in vitro, 52 it was also reported that FasL-or TNF-a-mediated signals can promote survival of eosinophils by activation of NF-kB-dependent target genes. 52,53 Similarly, TNF-a was shown to activate the NF-kB pathway in ex vivo isolated human eosinophils, and it was proposed that a NF-kB-induced protein protects the cell from caspase-dependent apoptosis. 54,55 In addition, it was shown that NF-kB-induced secretion of IL-6 promotes autocrine activation of PI3K and subsequent expression of the antiapoptotic protein Mcl-1 in neutrophils 56 .…”
Section: Discussionmentioning
confidence: 99%